2016
DOI: 10.1111/ajt.13761
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Cytotoxic T Lymphocyte–Associated Protein 4–Immunoglobulin Treatment Reverses Ongoing Alloantibody Responses and Rescues Allografts From Acute Rejection

Abstract: Antibody-mediated rejection has emerged as the leading cause of late graft loss in kidney transplant recipients, and inhibition of donor-specific antibody production should lead to improved transplant outcomes. The fusion protein CTLA4-Ig blocks T-cell activation and consequently inhibits T-dependent B cell antibody production, and the current paradigm is that CTLA4-Ig is effective on naïve T cells and less so on activated or memory T cells. In this study, we used a mouse model of allo-sensitization to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 59 publications
5
55
0
Order By: Relevance
“…We and others have reported that CTLA4-Ig inhibits early T cell-dependent alloantibody responses as well as recall responses (15)(16)(17)(18). In this study, we extend those observations by characterizing the impact of extended CTLA4-Ig treatment on graft-reactive memory T cell responses.…”
Section: Cd57supporting
confidence: 69%
See 1 more Smart Citation
“…We and others have reported that CTLA4-Ig inhibits early T cell-dependent alloantibody responses as well as recall responses (15)(16)(17)(18). In this study, we extend those observations by characterizing the impact of extended CTLA4-Ig treatment on graft-reactive memory T cell responses.…”
Section: Cd57supporting
confidence: 69%
“…Donor B/c.2W-OVA-transgenic mice were backcrossed from B/6-2W-OVA mice for 6 to 9 generations. Heart transplantation, flow cytometry, and H&E staining were performed as previously reported (18). In some experiments, B/6 mice sensitized with B/c-2W-OVA or B/c splenocytes, received, upon B/c-2W-OVA heart transplantation, 500 μg of CTLA4-Ig/mouse (abatacept; Bristol-Myers Squibb) on days -2, 0, and 2 (i.v.…”
Section: Methodsmentioning
confidence: 99%
“…Using mouse pMHC multimers to track endogenous graftreactive T cells specific for model donor antigens (Young et al, 2016), we here report that during productive alloimmunity, endogenous CD4 + and CD8 + T cells increased in avidity for alloantigen at the population level. In contrast, following therapeutically induced peripheral tolerance, the avidity profile of T cell populations remained low and comparable to that of naive populations, despite upregulation of CD44 expression by tolerant T cells.…”
Section: Introductionmentioning
confidence: 97%
“…Treatment of mice with cytotoxic T lymphocyte-associated protein-4-Ig (CTLA4-Ig) prevented alloantibody production when given in the first 2 weeks after sensitization (69,70). Similarly, the CTLA4-Ig fusion protein belatacept reduced the risk of dnDSA formation in low-risk transplant patients (71).…”
Section: Neutrophil Marginationmentioning
confidence: 99%